Toward a sociological theory of religion and health - Blasi, Anthony J. (Religion and the Social Order, 2011)
Driven by funding agencies, empirical research in the social scientific study of health and medicine has grown in quantity and developed in quality. When it became evident, in what is now a tradition of inquiry, that people's religious activities had significant health consequences, a portion of that body of work began to focus more frequently on the relationship between health and religion. The field has reached a point where book-length summaries of empirical findings, especially those pertinent to older people, can identify independent, mediating, and dependent variables of interest. Every mediating variable, even if considered as a "control" variable, represents an explanation, a small theory of some kind. However, taken in granular form, as it were, the multiple theories do not comprise mid-level theory, let alone a general theoretical framework. This volume seeks to move toward more general theoretical development.